Evaluating common drivers for color, iron and organic carbon in Swedish watercourses - Johan Temnerud; Julia K. Hytteborn; Martyn N. Futter; Stephan J. Köhler (Ambio, 2014)

Headwater biodiversity among different levels of stream habitat hierarchy - Emma Göthe; Nikolai Friberg; Maria Kahlert; Johan Temnerud; Leonard Sandin (Biodiversity and Conservation, 2014)

Selective decay of terrestrial organic carbon during transport from land to sea - Gesa A. Weyhenmeyer; Mats Fröberg; Erik Karltun; Maria Khalili; Dolly Kothawala; Johan Temnerud; Lars J. Tranvik (Global Change Biology, 2012)
Numerous studies have estimated carbon exchanges at the land–atmosphere interface, more recently also including estimates at the freshwater–atmosphere interface. Less attention has been paid to lateral carbon fluxes, in particular to the fate of terrestrial carbon during transport from soils via surface waters to the sea. Using extensive datasets on soil, lake and river mouth chemistry of the boreal/hemiboreal region we determined organic carbon ( OC ) stocks of the O horizon from catchment soils, annual OC transports through more than 700 lakes ( OC lakeflux ) and the total annual OC transport at S weden's 53 river mouths ( OC seaflux ). We show here that a minimum of 0.03–0.87% yr −1 of the OC soil stocks need to be exported to lakes in order to sustain the annual OC lakeflux . Across S weden we estimated a total OC lakeflux of ~2.9 Mtonne yr −1 , which corresponds to ~10% of S weden's total terrestrial net ecosystem production, and it is over 50% higher than the total OC seaflux . The OC loss during transport to the sea follows a simple exponential decay with an OC half‐life of ~12 years. Water colour, a proxy often used for dissolved humic matter, is similarly lost exponentially but about twice as fast as OC . Thus, we found a selective loss of the coloured portion of soil‐derived OC during its transport through inland waters, prior to being discharged into the sea. The selective loss is water residence time dependent, resulting in that the faster the water flows through the landscape the less OC and colour is lost. We conclude that increases in runoff will result in less efficient losses of OC , and particularly of colour, if the time for OC transformations in the landscape shortens. Consequently, OC reaching the sea is likely to become more coloured, and less processed, which can have far‐reaching effects on biogeochemical cycles.

Riparian Zone Influence on Stream Water Dissolved Organic Carbon Concentrations at the Swedish Integrated Monitoring Sites - Mattias Winterdahl; Johan Temnerud; Martyn N. Futter; Stefan Löfgren; Filip Moldan; Kevin Bishop (Ambio, 2011)

Thirty‐five years of synchrony in the organic matter concentrations of Swedish rivers explained by variation in flow and sulphate - MARTIN ERLANDSSON; ISHI BUFFAM; JENS FÖLSTER; HJALMAR LAUDON; JOHAN TEMNERUD; GESA A. WEYHENMEYER; KEVIN BISHOP (Global Change Biology, 2008)
Increasing concentrations of organic matter (OM) in surface waters have been noted over large parts of the boreal/nemoral zone in Europe and North America. This has raised questions about the causes and the likelihood of further increases. A number of drivers have been proposed, including temperature, hydrology, as well as ‐ and Cl − deposition. The data reported so far, however, have been insufficient to define the relative importance of different drivers in landscapes where they interact. Thirty‐five years of monthly measurements of absorbance and chemical oxygen demand (COD), two common proxies for OM, from 28 large Scandinavian catchments provide an unprecedented opportunity to resolve the importance of hypothesized drivers. For 21 of the catchments, there are 18 years of total organic carbon (TOC) measurements as well. Despite the heterogeneity of the catchments with regards to climate, size and land use, there is a high degree of synchronicity in OM across the entire region. Rivers go from widespread trends of decreasing OM to increasing trends and back again three times in the 35‐year record. This synchronicity in decadal scale oscillations and long‐term trends suggest a common set of dominant OM drivers in these landscapes. Here, we use regression models to test the importance of different potential drivers. We show that flow and together can predict most of the interannual variability in OM proxies, up to 88% for absorbance, up to 78% for COD. Two other candidate drivers, air temperature and Cl − , add little explanatory value. Declines in anthropogenic since the mid‐1970s are thus related to the observed OM increases in Scandinavia, but, in contrast to many recent studies, flow emerges as an even more important driver of OM variability. Stabilizing levels also mean that hydrology is likely to be the major driver of future variability and trends in OM.